2022
DOI: 10.1111/nicc.12833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of awake‐prone positioning on oxygenation and physiological outcomes in non‐intubated patients with COVID‐19: A randomized controlled trial

Abstract: Background Prone positioning is a well‐known supportive approach for increasing oxygenation and reducing mortality in non‐COVID‐19 patients with moderate to severe acute respiratory distress syndrome. However, studies highlighting the effects of proning in patients with COVID‐19 are limited. Aim To investigate the effects of awake‐prone positioning (APP) on oxygenation and physiological outcomes in non‐intubated patients with COVID‐19. Study Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
0
15
0
3
Order By: Relevance
“…None of the studies were powered to compare the differences in mortality. Seven other studies primarily investigated oxygenation improvement [ 49 52 , 54 56 ]. Of the five large sample size studies [ 44 48 ], two only enrolled patients with mild AHRF and treated with conventional oxygen therapy [ 45 , 47 ], while a large meta-trial confined enrolment to patients with moderate to severe AHRF who received HFNC oxygen therapy [ 44 ], while the remaining two studies had mixed patient populations [ 46 , 48 ].…”
Section: Insights From Covid-19 Studiesmentioning
confidence: 99%
“…None of the studies were powered to compare the differences in mortality. Seven other studies primarily investigated oxygenation improvement [ 49 52 , 54 56 ]. Of the five large sample size studies [ 44 48 ], two only enrolled patients with mild AHRF and treated with conventional oxygen therapy [ 45 , 47 ], while a large meta-trial confined enrolment to patients with moderate to severe AHRF who received HFNC oxygen therapy [ 44 ], while the remaining two studies had mixed patient populations [ 46 , 48 ].…”
Section: Insights From Covid-19 Studiesmentioning
confidence: 99%
“…Currently, 11 randomized controlled trials (RCTs) [7 ▪▪ −10 ▪▪ ,11,17] and one nonrandomized controlled trial [18 ▪▪ ] have been published on using APP to treat hospitalized patients with COVID-19-induced AHRF. Early this year, a meta-analysis that included nine of those RCTs with one unpublished RCT reported a lower risk of intubation in the APP group than in the group with standard care (relative risk [RR] 0.84 [95% confidence interval (CI) 0.72–0.97]) but no difference in the risk of death was observed [6 ▪▪ ].…”
Section: What Are the Effects Of Awake Prone Positioning On Patients ...mentioning
confidence: 99%
“…Of note, among the 11 published RCTs [7 ▪▪ −10 ▪▪ ,11–17] and one nonrandomized controlled trial [18 ▪▪ ], none of them reported a significantly reduced intubation rate except for the meta-trial that had a daily APP duration of 5 h/day [7 ▪▪ ]. Besides the smaller sample size, poorer adherence to APP and shorter duration (varied from 1.6 h/day [11] to 4.2 h/day [18 ▪▪ ]) might help explain the lack of statistically significant differences in those studies [8 ▪▪ −10 ▪▪ ,11–17,18 ▪▪ ]. As such, a minimum APP duration of 8 h/day is recommended.…”
Section: How Long Should Patients Stay In Prone Position Every Day?mentioning
confidence: 99%
See 2 more Smart Citations